Farm characteristics and cradle to farm gate beef carbon footprint of grass-based beef cattle fattening farms in Colombia - Méndez, Johana Leiva; Gonzalez-Quintero, Ricardo; Sánchez Pinzón, María Solange; Gallego, Belloncy; Echeverry Tangarife, Maribel; Duque Ramírez, Antonio; Mojica, Sebastián Castrillón; Barahona Rosales, Rolando (Instituto de Tecnologia do Paraná (Tecpar), 2025)
Abstract The proper management of agricultural systems requires knowledge of their characteristics, which is also necessary to optimize their productivity and reduce their environmental impact. The cradle-to-farm gate carbon footprint (CF) of 39 beef production farms located in nine departments of Colombia was estimated using the life cycle assessment (LCA) methodology. Farms were characterized with respect to livestock composition and management, pasture management practices, and productive (live weight gain, LWG) and reproductive information. Average daily gain (ADG) was the variable that most influenced the magnitude of the CF. By grouping by their main characteristics, a farm cluster containing 56% of the farms showed an average footprint of 11.6 kg CO2-eq kgLWG-1, lower than the average for Colombian farms (15.5 kg CO2-eq kgLWG-1) and a ADG of 0,49 kg d-1. In turn, a second farm cluster (44% of the farms) had an average footprint of 21.1 kg CO2-eq kgLWG-1 and a ADG of 0,37 kg d-1. In general, farms with higher animal productivity and stocking rate, had also greater use of fossil fuels and electricity, and also greater area of the farm as forests, all of which was associated to lower CF. Under the conditions evaluated, to produce meat with lower CF, strategies designed to increase ADG must be promoted, especially those related to adequate grazing management.